(untitled) (Computer systems and information technologies, 2023)
Theoretical optimization models assume the presence of a single criterion. Therefore, the solution of the problem by the method of vecto (multi-criteria) optimization is of particular interest in the problems of cybersecurity and information security. Especially when it is necessary to evaluate the correctness of the made decisions (CMD). In the paper this problem is solved so that it can be asserted that the decision was made correctly in this particular case when solving a problem while ensuring the information security of a particular object.